A framework for creating an ICT knowledge hub in Zimbabwe: a holistic approach in fostering economic growth: Paper presented at 11th Zimbabwe International Research Symposium - Mahlangu, Gilbert; Musungwini, Samuel; Sibanda, Mavellas (Research Council of Zimbabwe, 2018)
ICT knowledge hubs are important resources for a country to grow towards an innovative economy. Their growth has been viewed as a node point for techno-prenuership development and economic sustainability by many countries. The purpose of this study was to establish how Zimbabwe as a developing country should move towards the creation of an ICT knowledge hub that will promote economic growth in line with the Zimbabwe Agenda for Sustainable Socio-Economic Transformation (ZimAsset) economic blueprint crafted in 2013. A qualitative research design was used whereby literature was conducted to establish models for ICT Knowledge hub creation while two focus group discussions were held with academia, research agents and software developers to achieve face validity and indepth interviews were held with officials from The Ministry of ICT Postal and Courier services. The consensus was reached on the need for creating a focal point which will act as a cyberport where ICT driven solutions can be obtained based on the industry needs. The focus group discussions settled for four components in creating an ICT knowledge hub. These are planning function, development function, management function and co-ordinating function. The research also established that the Ministry of ICT and Courier services in Zimbabwe has set up an innovation fund to encourage and reward innovation and craftsmanship in Zimbabwe mainly targeted at the youths. The government acquired the high performance computing facility which is stationed at the University of Zimbabwe. The ICT hub should be used to facilitate access and use of this resource. Every country should therefore strive to create its own centre of innovation which enables it to gain maximum utility from its indigenous people in order to fully utilise ICTs for industry development and spearhead economic growth. The study recommends that there is need for establishing an ICT Knowledge hub in the country.